Effects of supplementing corn silage to fall-calving cows grazing tall fescue or bermudagrass, on cow and calf performance and physiology - Banks, James Wyatt Lang (Kansas State University, 2024)
Cow-calf operations across the U.S. serve as the foundation for the nation’s beef cattle industry. Cattle effectively convert forages to high quality protein by grazing pastureland often not suitable for crop production. To maximize grazing potential, producer cognizance of available forage types, their growth patterns, and nutritional value are crucial. For instance, the cool-season perennial, tall fescue, follows a bimodal growth pattern and reaches optimal forage quality in the early spring. Conversely, a warm-season perennial like bermudagrass has a unimodal forage growth curve, with forage quality peaking in early summer. Fescue has acquired the reputation of a “miracle forage”, capable of withstanding the environmental stressors of drought, insect predation, and poor soil conditions. However, the fungal endophyte that inhabits tall fescue produces ergot alkaloids, that when consumed are responsible for negative impacts on weight gain, reproduction, and endocrine function in cattle. Supplemental feeding, transitioning to a fall calving system, and the development of endophyte-free and non-toxic strands of fescue have been introduced as potential avenues for fescue toxicosis mitigation. Supplemental feeding has also been proven to improve grazed forage savings in drought management situations. Unfortunately, limited research has been conducted to evaluate cow and forage performance, and cow physiology, when supplementing corn silage to cattle grazing toxic fescue. Transitioning to bermudagrass for grazing cattle during the summer months may prove effective in mitigating drought and avoiding fescue toxicosis when ergot concentrations and ambient temperatures are highest. However, unlike fescue, little is known about the physiological effects of grazing bermudagrass, let alone how supplemental feeding can impact cattle grazing bermudagrass. Chapter one is a review of the literature surrounding forage, fescue toxicosis, and supplemental feeding. Chapter two is an evaluation of the physiological impacts of supplemental feeding late-gestation fall calving cows and calves on different fescue cultivars. Chapter three investigates the supplemental feeding of late-gestation fall calving cows and calves on bermudagrass pastures.
Keywords: Bermudagrass; Fall-calving cow; Fescue; Late gestation; Performance; Physiology